Soft Robots: Fast‐Response, Stiffness‐Tunable Soft Actuator by Hybrid Multimaterial 3D Printing (Adv. Funct. Mater. 15/2019). (9th April 2019) - Zhang, Yuan‐Fang; Zhang, Ningbin; Hingorani, Hardik; Ding, Ningyuan; Wang, Dong; Yuan, Chao; Zhang, Biao; Gu, Guoying; Ge, Qi
Abstract : In article number1806698, Guoying Gu, Qi Ge, and co‐workers develop a paradigm to design and manufacture fast‐response, stiffness‐tunable (FRST) soft actuators via hybrid multimaterial 3D printing. The robotic gripper with three FRST actuators demonstrates a high load capacity and shape adaptivity by lifting objects with arbitrary shapes and various weights spanning from less than 10 g to 1.5 kg.